2023
DOI: 10.1186/s13567-023-01156-y
|View full text |Cite
|
Sign up to set email alerts
|

Priming of the murine mammary gland with Staphylococcus chromogenes IM reduces bacterial growth of Streptococcus uberis: a proof-of-concept study

Abstract: Streptococcus uberis is a major causative agent of bovine mastitis, an inflammation of the mammary gland with substantial economic consequences. To reduce antibiotic use in animal agriculture, alternative strategies to treat or prevent mastitis are being investigated. Bovine-associated non-aureus staphylococci are proposed in that respect due to their capacity to inhibit the in vitro growth of S. uberis. We demonstrate that priming the murine mammary gland with Staphylococcus chromogenes IM reduces S. uberis g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Cloxacillin, being an isoxazolyl penicillin, needs to be incorporated into the cell wall of multiplying Gram-positive bacteria to effectively eliminate them (Kim et al 2023 ). As a result, the CFU levels in the cloxacillin treatment groups, with or without addition of endolysin NC5, were as expected not completely reduced to the limit of detection after only 4 h. Nevertheless, in our previous in vitro study, an accelerated reduction in S. uberis CFUs was observed in raw milk between the 4 and 8 h time points for the supplemental strategy (Vander Elst et al 2023b ). Therefore, in this preclinical in vivo study, we deliberately choose to evaluate the combination treatment after only 4 h to specifically capture the small discrepancies between the experimental groups mid-treatment (Woodward and Whittem 2019 ).…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Cloxacillin, being an isoxazolyl penicillin, needs to be incorporated into the cell wall of multiplying Gram-positive bacteria to effectively eliminate them (Kim et al 2023 ). As a result, the CFU levels in the cloxacillin treatment groups, with or without addition of endolysin NC5, were as expected not completely reduced to the limit of detection after only 4 h. Nevertheless, in our previous in vitro study, an accelerated reduction in S. uberis CFUs was observed in raw milk between the 4 and 8 h time points for the supplemental strategy (Vander Elst et al 2023b ). Therefore, in this preclinical in vivo study, we deliberately choose to evaluate the combination treatment after only 4 h to specifically capture the small discrepancies between the experimental groups mid-treatment (Woodward and Whittem 2019 ).…”
Section: Discussionsupporting
confidence: 65%
“…1 ). Therefore, mice ( n = 18) were inoculated intramammarily with 10 3 CFU of a selected S. uberis field isolate belonging to the pathotype GGC ST-5, which our group previously isolated from a clinical bovine mastitis case (Vander Elst et al 2023b ). The bacterial load as well as the influx of neutrophils was subsequently evaluated at 8, 12, and 24 h post-infection (p.i.)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, even though pre-colonization of the udder by some members of NAS species seems protective against colonization by major mastitis pathogens, some NAS species themselves were isolated and identified as the etiology of mastitis and shown to be responsible for milk production losses ( 94 , 142 , 146 ). It has also been shown that priming the murine mammary glands with S. chromogenes induced innate responses that reduced the growth of S. uberis ( 161 ). However, the authors did not clearly demonstrate if priming with S. chromogenes itself induced mastitis rather than enhancing protective innate immunity.…”
Section: Bovine Staphylococcal Mastitismentioning
confidence: 99%